PENGARUH PDB (PRODUK DOMESTIK BRUTO) DAN NILAI TUKAR TERHADAP EKSPOR INDONESIA (2004-2011) - B01109115, Sri Rahayu (Jurnal Pembangunan dan Pemerataan, 2014)
Direct export can improve countries income, and it describes the economy development and prosperity achievement. By raising the economy level and achieving prosperity, it will drive the development especially in economy. Export is essential thing in economy, because it estabilishes and controls the balance of payment in country, besides export describes additional of funds from national circulation income which gives more income and real output. This study aims to know the influence of PDB (Product Domestic Bruto) and exchange rate toward Indonesian export (2004-2011). Analisys model used in this study is regresi linier berganda, testing t to examine partially and testing f to examine simultaneously. From this study, the writer concluded that there is linear relation between PBD (Product Domestic Bruto) and the export, and there is significant negative influence between exchange rate and the export during 2004 to 2011. Key word : PBD, Exchange Rate, Export